Technology, Science and Culture A Global Vision, Volume III - Ricardo Hernández, Luis; Alejandro Serrano Meneses, Martín (IntechOpen, 2022)
From the success of the first and second volume of this series, we are enthusiastic to continue our discussions on research topics related to the fields of Food Science, Intelligent Systems, Molecular Biomedicine, Water Science, and Creation and Theories of Culture. Our aims are to discuss the newest topics, theories, and research methods in each of the mentioned fields, to promote debates among top researchers and graduate students and to generate collaborative works among them.